Iraqi Vernacularism in Contemporary Art: (Mahmoud Fahmi as a Case Study of Cultural Patriotism) - Dr. Nasser Hajjaj (Journal of Arts, Literature, Humanities and Social Sciences, 2025)
This paper explores the theory of Vernacularism within the framework of Iraqi visual arts, focusing on the works of Mahmoud Fahmi - one of the most vivid contemporary artists to engage in vernacular expression. Fahmi’s art celebrates the architectural, social, and folkloric vocabulary of Iraq through highly symbolic visual language. By employing modern artistic techniques such as stylized realism, abstract figuration, and textural layering, his works revive elements like the Shanāshīl, brick alleys, alley cats, minarets, traditional garments, and vernacular objects. Positioned within a broader movement of Iraqi Vernacularism, this paper contextualizes Fahmi’s work alongside that of earlier pioneers like Shakir Hassan Al Said, Faeq Hassan, and Hafidh al-Droubi, arguing that Vernacularism is both an aesthetic and ideological position rooted in cultural patriotism and resistance to erasure.